MASALAH, POTENSI, DAN SUMBER DAYA SOSIAL DAERAH TERTINGGAL (Studi Kasus Desa Buwunmas, Kecamatan Sekotong - Kabupaten Lombok Barat) - Sutaat Sutaat (Puslitbangkesos Kementerian Sosial RI, 2010)
Remote area has been described as limited facilities in terms of both social and economy. The area has also less reached by development program. Because of thet then one among varies characters of remote area is the high numbers of poor people and less human resources. This research has tried to find varies infonus about remote areas. Moreover, it will recommend for government in order to overcome the problem of remote area. The research has been conducted in Buwunmas rural, district Sekotong, Lombok Barat. Tile research shows that main problem of the people is poverty, that impacts on the inadequate dweller, neglect, and problems of migrant worker family. Even though Buwunmas has enough natural resources but has not enjoyed by its people. The gold mining and the result has still for the capital owners. The impacts of programs that have ever done at this rural have also not brought their welfare. This case is related to inadequate study of local condition. Base on this finding, its recommended to conduct social deoelopnieu tprogram, infrastructure development, and alternatives developments program such. as social empowerment and tourism development.